2015
DOI: 10.1007/s00122-015-2523-z
|View full text |Cite
|
Sign up to set email alerts
|

Allelic variants in the PRR37 gene and the human-mediated dispersal and diversification of sorghum

Abstract: Allele phylogenetic analysis of the sorghum flowering-time gene PRR37 provided new insight into the human-mediated selection of a key adaptive gene that occurred during sorghum's diversification and worldwide dispersal. The domestication and spread of the tropical cereal sorghum is associated with the historic movement of humans. We show that an allelic series at PRR37 (pseudo-response regulator 37), a circadian clock-associated transcription factor, was selected in long-day ecosystems worldwide to permit flor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 39 publications
1
21
0
2
Order By: Relevance
“…The PRR gene family was first discovered in Arabidopsis, in which three of five members play redundant roles in flowering under long-day conditions (Nakamichi et al 2007). PRR genes also influence geographical adaptation in several crops (Klein et al 2015;Koo et al 2013;Turner et al 2005). Recent study suggested two homologous PRR3 genes controlling flowering and maturity were sequentially selected during soybean domestication (Lu et al 2020).…”
Section: Siprr37 Contributed To the Local Adaptation To The Northeastmentioning
confidence: 99%
“…The PRR gene family was first discovered in Arabidopsis, in which three of five members play redundant roles in flowering under long-day conditions (Nakamichi et al 2007). PRR genes also influence geographical adaptation in several crops (Klein et al 2015;Koo et al 2013;Turner et al 2005). Recent study suggested two homologous PRR3 genes controlling flowering and maturity were sequentially selected during soybean domestication (Lu et al 2020).…”
Section: Siprr37 Contributed To the Local Adaptation To The Northeastmentioning
confidence: 99%
“…In sorghum, there are many loss-of-function alleles encoding truncated PRR37 protein. Each PRR37 allelic variant could be traced to specific geographic location or specialized agronomic type (Klein et al, 2015), indicative of human selection. In this study, when we analyzed the variation of Glyma.12G073900 at nucleotide 2088 in 642 soybean accessions, it was found that JLCLH homologous type mostly exists in wild soybeans and landrace, whereas CN homozygous type are mostly distributed in improved cultivar.…”
Section: Discussionmentioning
confidence: 99%
“…Sequence analysis revealed that the most significant QTL corresponds to the known Ma 1 gene on chromosome 6 ( PRR37 , Sobic.006G057866), encoding a pseudoresponse regulator protein ( 28 ). A single adenine insertion in the third exon of Tx430 allele was identified that led to a premature stop codon and nonfunctional protein ( prr37 Feterrita ) ( 29 ) ( Fig. 5 and SI Appendix , Fig.…”
Section: Genetic Determinants Of Flowering Timementioning
confidence: 99%